Changes in Textural and Geo-Chemical Features of Alluvia in the Western Part of the Lublin Upland Over the Past 1000 Years - Zgłobicki, Wojciech; Ryżak, Magdalena; Bieganowski, Andrzej (Quaestiones Geographicae, 2011)
In the study the authors analysed the diversity of the textural indices and selected geo-chemical features of sediments that accumulated in the bottoms of valleys in the western part of the Lublin Upland over the past 1000 years. Detailed studies were performed for six profiles with known stratigraphy. The sediments studied varied little in terms of textural features, with a general trend for particle diameters to increase as the depth increased. The characteristics of the sediments indicate a significant role of material supply from the slope systems (mainly gullies) to the bottoms of river valleys. The heavy metal content was characterised by greater vertical variation. In most of the profiles, the youngest deposits were characterised by greater levels of Cd, Cu, Pb and Zn, with enrichment indexes at an average of 1.5-2.5. The observed diversity of the features of sediments, particularly the geo-chemical features, should be attributed to the effect of human activity in the area studied.